Toward carbon neutrality: The impact of manufacturing agglomeration on total factor energy efficiency - Jiang, Hong; Chen, Zhenhuan; Zhao, Wencheng; Wang, Fayao; Xia, Jing; Chen, Zhenyu (Frontiers in Environmental Science, 2023)
Improving energy efficiency is an effective way to achieve carbon neutrality in the context of growing green economy advocacy in both academia and government. This paper analyzes the impact mechanism of manufacturing agglomeration on total factor energy efficiency. Based on this, there are thirty provinces (autonomous regions and municipalities) in China from 2002 to 2017 panel data. Used DEA game cross-efficiency model to calculate inter-provincial Current state of energy efficiency. Constructing a spatial Durbin model, using adjacent space weight matrix, geographic distance weight matrix and economic distance weight matrix to study the impact of manufacturing agglomeration on total factor energy efficiency. The results show that under different spatial weights, the inter-provincial total factor energy efficiency has a significant spatial dependence; under the three spatial weights, there is a “U”-shaped relationship between manufacturing agglomeration and total factor energy efficiency. Industrial agglomeration has obvious spatial spillover effects on total factor energy efficiency, and the spillover effects under the weight of geographic distance are higher than other spatial weights; during the sample period, the direct, indirect and total effects of the manufacturing industry have an impact on energy efficiency. It all has a negative number indicating that there is a “crowding effect” in manufacturing agglomeration, and it has an inhibitory effect on energy efficiency.